Sebaceous Carcinoma of the Eyelid: Proposed Nomenclature for Multifocal and Multicentric Disease. Issue 2 (20th October 2022) - Magazin, Maja; Dalvin, Lauren A.; Salomao, Diva R.; Castner, Nicholas B.; Halbach, Caroline; Tooley, Andrea A.
Abstract : Purpose: To review clinical presentations of periocular sebaceous carcinoma (SC) and introduce standardized nomenclature for multicentric and multifocal disease presentation. Methods: A comprehensive PubMed/Medline search was conducted to identify all articles reporting periocular multicentric or multifocal SC presentations. The authors also highlight an additional case of SC presenting with 2 clinically distinct tumor foci and complete secondary invasion of the lacrimal gland. Results: This review summarizes clinical presentations of periocular SC exhibiting discrete foci of microinvasion reported in the literature. Discrete microinvasion was associated with high rates of misdiagnosis (80%), simultaneous involvement of both upper and lower eyelids (80%), pagetoid spread (80%), multinodular growth (33%), local tumor spread (60%), previous eyelid manipulation (40%), and local recurrence (40%). Eyelid multifocality with clinically discrete nodules (42%) was associated with more advanced disease including orbital extension and regional invasion (80%). Conclusions: Despite previous reported associations with poorer outcomes, there is no consensus in the definition or nomenclature for discrete microinvasive or clinical disease presentations in periocular SC. The authors recommend defining multicentric disease as discrete foci of microinvasive tumor with basement membrane disruption and multifocal disease as discrete clinically evident nodules involving both the upper and lower eyelids. Differentiating between discrete microinvasive (multicentric) and clinically nodular (multifocal) disease may improve risk stratification to most accurately identify patients who require more aggressive management and surveillance. Abstract : To establish standardized nomenclature for more accurate classification of periocular sebaceous carcinoma, the authors recommend "multicentric" to describe discrete foci of histologic invasion, reserving the term "multifocal" for clinically evident nodules involving both upper and lower eyelids.